PENYULUHAN TENTANG BEBAN GANDA PEREMPUAN DALAM BEKERJA PADA LINGKUP RUMAH TANGGA DALAM PERSPEKTIF HAM DAN KAJIANNYA TERHADAP KESETARAAN GENDER - Saptosih Ismiati (Jurnal Abdimas Bina Bangsa, 2023)
Gender equality is something that women really want. In existing social constructions, gender roles cannot stand alone, but their existence has been influenced by the characteristics that society has assumed for men and women. From the gender injustice that arises in the midst of our society, especially those that are still thick with patriarchal culture, it certainly causes women not to have strong freedom as well as men. The problem that often occurs is the double workload in the family, especially the social assumption that has applied the position that women are individuals who are suitable for doing domestic work is the trigger for the double workload. Though housework should not only be a woman's obligation but the responsibility is the responsibility of every family member, in particular, this study will examine the problems experienced by women. The research method used is a descriptive method of analysis, which uses a normatic juridical approachF is legal research conducted by conducting research on literature materials consisting of primary, secondary and tertiary materials.